ASSESSMENT OF THE EFFECTIVENESS OF ONLINE PHYSICAL EDUCATION - Iqbolakhon Khasanboy qizi Abdiolimova; Abduraxmanov Saydillo Khakimovich (Proximus Journal Publishing, 2025)
This article examines the effectiveness of online physical education (PE) programs, especially in the wake of the COVID-19 pandemic. It explores key indicators such as student engagement, learning outcomes, physical activity levels, and instructor adaptability. The article also discusses challenges and best practices for enhancing the quality and impact of virtual PE classes.
Keywords: Online physical education; distance learning; physical activity